2013
DOI: 10.1016/j.brainres.2013.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of SNPs in CHRNA3/B4 intergenic region associated with drug behaviors

Abstract: The cluster of human neuronal nicotinic receptor genes (CHRNA5/A3/B4) (15q25.1) has been associated with a variety of smoking and drug-related behaviors, as well as risk for lung cancer. CHRNA3/B4 intergenic single nucleotide polymorphisms (SNPs) rs1948 and rs8023462 have been associated with early initiation of alcohol and tobacco use, and rs6495309 has been associated with nicotine dependence and risk for lung cancer. An in vitro luciferase expression assay was used to determine whether these SNPs and surrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 64 publications
1
23
0
Order By: Relevance
“…The C allele of this same SNP has been previously associated with externalizing and delinquent behaviors (Stephens et al, 2012). Remarkably, experimental studies demonstrated that the GATA transcription factors, involved in fine receptor regulation during development, are only capable of binding when the C allele is present (Flora et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The C allele of this same SNP has been previously associated with externalizing and delinquent behaviors (Stephens et al, 2012). Remarkably, experimental studies demonstrated that the GATA transcription factors, involved in fine receptor regulation during development, are only capable of binding when the C allele is present (Flora et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…Flora and collaborators suggest that this transcription factor might play a role in controlling nicotinic receptor subunit expression in specific cell lines and developmental stages, which could be negatively affected by tobacco exposure (Flora et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The four nonsynonymous variants classified as probably damaging by Polyphen-2 may be of interest for further analysis. We found twice as many variants in CHRNA6 introns and UTRs in cases compared to control, which may lead to subtle differences in transcription (Ehringer et al, 2010; Flora et al, 2013; Gallego et al, 2013; Kamens et al, 2015). …”
Section: Discussionmentioning
confidence: 72%
“…Non-coding regions in the Chrn genes in rodents have been shown to play an important role in gene regulation (Bruschweiler-Li et al, 2010; McDonough and Deneris, 1997; McDonough et al, 2000; Scofield et al, 2010; Xu et al, 2006). Moreover, in vitro gene expression studies using cell culture models to examine human genetic variants in the non-coding regions of CHRN genes have demonstrated differential functional effects for SNP alleles (Ehringer et al, 2010; Flora et al, 2013; Gallego et al, 2013; Kamens et al, 2015). Because expression of individual nicotinic receptor subunits is tightly regulated, both temporally and spatially (Albuquerque et al, 2009; Gotti et al, 2006, 2009), the importance of genetic variants in non-coding regions must also be explored.…”
Section: Introductionmentioning
confidence: 99%
“…The α5 risk variant, rs16969968 G/A, causes an Asp398Asn amino acid substitution, and the risk allele (Asn398) produces hypofunctional α5-containing nAChRs with reduced Ca 2+ permeability and faster desensitization rates than non-risk alleles (Bierut et al, 2008; Kuryatow et al, 2011). Other polymorphisms are associated with different levels of α5 or α3 mRNA (Wang, 2009), and the functional significance of several other gene variants in the CHRNA5/A3/B4 gene cluster is currently being investigated (Flora et al, 2013). …”
Section: Nicotinic Receptor Subunits and Their Influence On Nicotimentioning
confidence: 99%